2008
DOI: 10.1007/s10368-008-0110-3
|View full text |Cite
|
Sign up to set email alerts
|

The stability and growth pact, fiscal policy institutions and stabilization in Europe

Abstract: Ever since its inception, the EMU has been subject to controversy. The fiscal policy rules embedded in the Maastricht Treaty, and clarified in the Stability and Growth Pact (SGP), are probably the most contentious. The SGP has constantly been accused of being too rigid and of forcing procyclicality in fiscal policy. However, in an influential paper Galí and Perotti (2003) concluded that discretionary fiscal policy has actually become more countercyclical in EMU countries since the Maastricht Treaty. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…As described above, acyclicality in the SGP period was also reported by other studies (Marinheiro, 2007;Poplawski Ribeiro, 2009;Bénétrix and Lane, 2012). A decrease in the CAPB reaction to the debt was also observed (the coefficient is significant only with the IV-FE method), which points to a decrease in the debt stabilisation motive given the previous period.…”
Section: 311supporting
confidence: 84%
See 2 more Smart Citations
“…As described above, acyclicality in the SGP period was also reported by other studies (Marinheiro, 2007;Poplawski Ribeiro, 2009;Bénétrix and Lane, 2012). A decrease in the CAPB reaction to the debt was also observed (the coefficient is significant only with the IV-FE method), which points to a decrease in the debt stabilisation motive given the previous period.…”
Section: 311supporting
confidence: 84%
“…Conversely, Candelon et al (2008) and Fatás and Mihov (2009) established that discretionary policy in the period before and after the introduction of the EU fiscal rules was procyclical. On the other hand, studies by von Hagen and Wyplosz (2008), Marinheiro (2007), Poplawski Ribeiro (2009) and Bénétrix and Lane (2012) found that, in the Maastricht period, the discretionary fiscal policy had become countercyclical. After the entry to the EMU, Annett (2006), Marinheiro (2007) and Bénétrix and Lane (2012) observed a recurring procyclicality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Marinheiro (2010) adds another complete business cycle to the data under the SGP, and again finds that the forecasts of European fiscal authorities are systematically too optimistic. This evidence is not consistently strong across the set of 15 EU countries, but the bias is high for France, Italy and Portugal at all forecast horizons.…”
Section: Research On Official Fiscal Forecastingmentioning
confidence: 95%
“…These decisions comprise both the fiscal plan and its implementation. See, for example, Forni and Momigliano (2004), Cimadomo (2007), Marinheiro (2008, , Lewis (2009) andPina (2009). An early contribution is Strauch et al (2004), who use data on budget balances from the stability and convergence programmes over the period 1991-2002 and find that governments on average predict the future budget outcome fairly well.…”
Section: Introductionmentioning
confidence: 99%